Electrochemical Construction of Edge‐Contacted Metal‐Semiconductor Junctions with Low Contact Barrier. Issue 31 (26th June 2022) - Ping, Xiaofan; Liu, Weigang; Wu, Yueyang; Xu, Guanchen; Chen, Fengen; Li, Guangtao; Jiao, Liying
Abstract: 2D semiconductors, such as MoS2 have emerged as promising ultrathin channel materials for the further scaling of field‐effect transistors (FETs). However, the contact barrier at the metal‐2D semiconductor junctions still significantly limits the device's performance. By extending the application of electrochemical deposition in 2D electronics, a distinct approach is developed for constructing metal‐2D semiconductor junctions in an edge‐contacted configuration through the edge‐guided electrodeposition of varied metals. Both high‐resolution microscopic imaging and electrical transport measurements confirm the successful creation of high‐quality Pd‐2D MoS2 junctions in desired geometry by combining electrodeposition with lithographic patterning. FETs are fabricated on the obtained Pd‐2D MoS2 junctions and it is confirmed that these junctions exhibit a reduced contact barrier of ≈20 meV and extremely low contact resistance of 290 Ω µm and thus increase the averaged mobility of MoS2 FETs to ≈108 cm 2 V −1 s −1 . This approach paves a new way for the construction of metal‐semiconductor junctions and also demonstrates the great potential of the electrochemical deposition technique in 2D electronics. Abstract : A facile approach is developed for constructing high‐quality metal‐2D semiconductor junctions through the edge‐guided electrodeposition. Cross‐sectional imaging and transport measurements confirm the seamless contact of Pd with each layer of MoS2 greatly reduces the contact barrier to ≈20 meV and contact resistance to ≈290 Ω µm and thus significantly increases the performance of FETs with Pd nanowire edge contacts.